Enrico Vitelli: a cento anni dalla nascita - Selvini, Attilio (GEOmedia, 2019)
At Sapienza the chair of topography, immediately after the Second World War, was covered by Giovanni Boaga. The great scholar, who at the time was also Direttore Generale del Catasto e dei Servizi Tecnici Erariali, was looking for an assistant. He was introduced to a young Roman, tall and handsome, brilliantly graduated in engineering, who had served in the Royal Army as a lieutenant and was briefly in Stuttgart for relations with the Wehrmacht. The assignment was immediately given to him, but shortly after the engineer entered in the cadastral administration, where he would then conduct his entire career. The young man was Enrico Vitelli, born in 1919; military service in Pavia, where he met a kind and beautiful young lady of excellent family, who would later become his wife.